Biscuit Residue in the Nutrition of Laying Hens: Effects on Animal Health, Performance and Egg Quality - Rocha Gebert, Roger; dos Reis, João Henrique; Fortuoso, Bruno Fernando; Miotto Galli, Gabriela; Manente Boiago, Marcel; Paiano, Diovani; Pinto Kempka, Aniela; Dalamea Baldissera, Matheus; Schafer Da Silva, Aleksandro (Acta Scientiae Veterinariae, 2020)
Background: Corn and soybean meal are common ingredients used in poultry feed in order to supply the demand for energy and protein, respectively. Also, these ingredients directly influence the final price of the diets, and consequently, the final cost of production. A major problem is associated to the oscillation of these grains in some months of the year. Therefore, there is a need to search for nutritionally and economically viable alternatives to mitigate this problem. The aim was to evaluate whether the addition of biscuit residue could partially replace the use of corn in the feed of laying hens in order to obtain economic viability without impairment on production, egg quality and animal health. Materials, Methods & Results: The experiment was completely randomized and each repetition was considered one experimental unity. One hundred Hy-line brown 48 week-old chickens were allocated in cages and divided into five groups with four repetitions each, allocating five animals per cage. The group T0 was composed by animals that received the basal diet, i.e. without biscuit residue. The other groups were composed by increasing levels of biscuit residue to substitute corn i.e., group T7 (7% of biscuit residue), T14 (14% of biscuit residue), T21 (21% of biscuit residue) and T28 (28% of biscuit residue). Productive performance of the animals, egg quality, as well as analysis of blood parameters related to lipid metabolism, carbohydrates and proteins of birds were measured at the beginning of the experiment (day 0) and at the end of each cycle (days 21, 42 and 63 of experiment). Among the performance variables, only feed conversion was altered by biscuit residue, i.e., the feed conversion was lower in the groups that received the residue when compared to the control. The replacement of corn by biscuit residue did not affect laying rate (P > 0.05). Regarding egg quality, a less intense coloration was observed in the eggs of the treatments that received biscuit residue compared to the control group (P < 0.05), but without difference between treatments. Seric levels of uric acid were higher in the treatments that received biscuit residue in the days 21 and 42 compared to the control group, effect not seen in the third cycle (day 63). The cost () of feed reduced as the levels of inclusion of the biscuit residue in the diet were increased, with the control diet costing 0.244/kg, while 28% of biscuit inclusion lower its cost to 0.189/kg (22.3% lower). The final cost to produce a dozen eggs from each cycle was on average of 0.524, 0.415, 0.441, 0.397 and 0.332 for 0, 7, 14, 21 and 28% inclusion, respectively. Discussion: Residues of biscuit is widely used to feed swine, with positive results as an ingredient to attend the demand for energy. Even though the Brazilian Tables for Poultry and Swine include biscuit residue as a possible ingredient, there is a lack of scientific research in laying hens. These study was verified that the inclusion of biscuit residue (18.936%) is feasible, since it favors the productive performance of the animals, without adverse effects on their health; in addition, the inclusion of biscuit residue reduces dietary costs, as the cost of egg production. Whereas animal feed accounts for a large part of the production cost, the reduction in feed costs without impairment on animal productivity, is a key factor in animal farming. At certain times of the year, food can account for 80% of the production costs and consequently it influences the final price of the product in the market. In our study, we observed a significant reduction on total costs of diets that received biscuit residue, which occurred because a part of the energetic portion of the diet was supplied by the biscuit residue, and not by corn, which influenced the final price. Keywords: egg quality, biscuit residue, economic viability, nutrition.